Dilute Alloying to Implant Activation Centers in Nitride Electrocatalysts for Lithium–Sulfur Batteries - Liu, Quanbing; Wu, Yujie; Li, Dong; Peng, Yan‐Qi; Liu, Xinyan; Li, Bo‐Quan; Huang, Jia‐Qi; Peng, Hong‐Jie (Advanced materials (Weinheim), 2023)
Dilute alloying is an effective strategy to tune properties of solid catalysts but is rarely leveraged in complex reactions beyond small molecule conversion. In this work, dilute dopants are demonstrated to serve as activating centers to construct multiatom catalytic domains in metal nitride electrocatalysts for lithium–sulfur (Li–S) batteries, of which the sulfur cathode suffers from sluggish and complex conversion reactions. With titanium nitride (TiN) as a model system, the dilute cobalt alloying is shown to greatly improve the reaction kinetics while inducing negligible catalyst reconstruction. Compared to the pristine TiN, the dilute nitride alloy catalyst enables onefold increase in the high rate (2.0 C) capacities of Li–S batteries, as well as an impressively low cyclic decay rate of 0.17% at a sulfur loading of 4.0 mgS cm−2. This work opens up new opportunities toward the rational design of Li–S electrocatalysts by dilute alloying and also enlightens the understandings of complex domain‐catalyzed reactions in energy applications. Dilute alloying implants “activating” centers in nitride alloy electrocatalysts to boost lithium–sulfur (Li–S) batteries. Dilute Co dopants activate the surrounding N and Ti atoms to construct multiatom active domains for efficient bidirectional catalysis of S redox reactions. The corresponding dilute nitride alloy improves the reaction kinetics and electrochemical performance of Li–S batteries.